Effecient Photo-Stabilizers: By Using Medications As Ligands Connected to Oragontin(IV) Complexes - Alhaydary, Emad; Yousif, Emad (Al-Nahrain Journal of Science, 2021)
Organotin materials have several applications in industry and medicine since it uses to prepare medications. Moreover, it is used as photo-stabilizers for different plastic polymers such as polyvinyl chloride, polystyrene, and polyvinyl alcohol. Herein, it is going to focus on one application which is utilizing organotin complexes as photo-stabilizers of polyvinyl chloride. Since organotin (IV) can easily obtained by oxidizing organotin (II) that is more stable. Organotin (IV) can be designed in different forms depending on the number of organic and anion groups connected to the tin such as mono-organotin, di-, tri- and tetra- compounds. There are several applications of organotin materials in both industrial and medicine areas and in this paper, we are going to study some of a significant photo-stabilizers and their applications and we are going to highlight the using of organotin materials as photo-stabilizers of plastic polymers especially the PVC polymeric films.